The Inhaling Danger: How Air Pollution Affects Asthma Patients – A Phenomenological Study - Maryam Jan; Asrar Ali; Memoona Alam; Arooba Shahid; Nimra Gul (International Journal of Multidisciplinary Sciences and Arts, 2025)
Background: Asthma is a chronic respiratory condition characterized by episodes of airway construction, inflammation and mucus production. It affects millions of people worldwide and is influenced by various environmental factors such as air pollution. Objective: The objective of the article is to determine how asthmatic student health is impacted by air pollution, how asthma affects students' daily tasks and the awareness among asthma students about the risks caused by air pollution. Method: The results presented were obtained through a qualitative phenomenological study. The study was conducted on university students who are asthma patients. The sample consisted of 30 students patients with asthma experiences. Result: The findings revealed that effects of air pollution is one of the leading cause of asthma; triggering asthma and other respiratory health conditions. Conclusion: People with asthma especially students and young patients, will be further exposed to the threat of air pollution, and suffer from more serious health consequences. There have to be detailed assessments connected to the main air pollutants particulate matter (PM) and their causal relationship with respiratory disease, more in each country.